Transformasi Komunikasi dan Kolaborasi: Mendalami Microsoft Lync - Faiz Aqila Izura Atanta Berampu; Nurbaiti Nurbaiti (Maslahah : Jurnal Manajemen dan Ekonomi Syariah, 2024)
This article explores the critical role of communication and collaboration technologies, especially Microsoft Lync (now known as Microsoft Teams), in the context of a constantly changing business environment. This study aims to analyze how Microsoft Lync influences the transformation of business communication and its impact on today’s digital work environment. The introduction of Microsoft Lync, its evolution to Microsoft Teams, and its critical role in supporting modern business communications are discussed in detail. This study uses qualitative research methods by analyzing various sources such as scientific journals, books, and indexed trusted websites. This approach helps in understanding the transformation of communication and collaboration with Microsoft Lync as an intermediary tool. This article covers the benefits of Microsoft Lync, best practices for using it, and negative impacts to be aware of. The features of Microsoft Lync, how to use them, and their key role in enhancing communication and collaboration in business environments are emphasized. This article also provides insight into the history of Microsoft Lync’s evolution to Microsoft Teams, and the challenges that may arise in using it. By highlighting its important role, this research conveys a better understanding of how technologies such as Microsoft Lync have changed the way communication and collaboration work in the business world.